PENGAWAS SEKOLAH/MADRASAH: PENGEMBANGAN KARIR SEORANG PENDIDIK - Ryna Rachmawati (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
This paper describes career development for educators through different functional promotions. School/madrasah supervisor is one functional position that can be filled by educators as a career development form or promotion. Based on the regulations study related to the requirements assessment of being a school /madrasah supervisor and professional development based on competencies that must be possessed, it can be concluded that a school/madrasah supervisor is a career path that can be achieved by active, dynamic teachers which experienced as representatives or headmaster. Key Words: School /Madrasah Supervisor, Career Development.